Hukum Waris Adat dalam Memandang Kedudukan Hukum Anak Astra Pasca Perkawinan Kedua Orang Tua - Dedon Dianta; Audi Febriwidhia Aulia Putra (CV Rewang Rencang, 2024)
Basically, according to Balinese customary law, an Astra child's legal status will follow that of his father if his parents enter into a legal marriage. In fact, many problems arise in society because of the many incidents of children being born to women who have not experienced legal marriage. Therefore, this research aims to look at Astra children in their legal position after the existence of Law Number 1 of 1974 concerning Marriage and to define Balinese customary inheritance rights regarding the inheritance rights of Astra children. This research was carried out normatively by examining the applicable laws and regulations and relating them to what is happening in the Balinese community. In this regard, the legislation approach is the right approach to take. This research uses primary and secondary legal materials, which are then processed and analyzed using interpretive and systematic analysis. The position of Astra children in this research was concluded that after the enactment of Law no. 1 of 1974, then there is only a civil relationship with the mother's family or the mother herself. If the biological parents enter into a legal marriage in Bali, then the astra child's rights and status are purusa or following his father.